The globalizacion and development reader : perspectives on development and global change - Roberts, J. Timmons; Hite, Amy (Blackwell, 2007)
The Globalization and Development Reader" builds on the success of "From Modernization to Globalization," published by the editors in 2000 and used around the world. It provides an up-to-date primer and key reference for students, scholars, and development practitioners wishing to get up to speed quickly on the issues surrounding social change and development in the "Third World." Includes carefully excerpted samples from both classic and contemporary writings.